A Comprehensive Approach Office Core - Hinkle, Deborah (McGraw-Hill, 2002)
Fully covers all the skills required for the Word 2002, Excel 2002, and Access 2002 Microsoft Office User Specialist (MOUS) certifications at the Core level. Also covers basic PowerPoint skills (PowerPoint has only one MOUS skill level – the Comprehensive level.). Extremely comprehensive coverage. Extensive range of ancillaries provides instructors with a wide range of remediation, teaching, and assessment options. This text is suitable for a one- or two-semester course.